Features of the Early Hydrocarbon Accumulation and Its Effects on the Late Accumulation in Sandstone Reservoir: A Case Study of the Eocene Dongying Depression, Bohai Bay Basin - Wang, Miao; Chen, Yong; Song, Guoqi; Liu, Huimin; Wang, Yongshi; Zhang, Pengfei; Qiu, Yibo; Chen, Tao; Li, Jiyan; Liu, Xinjin; Liu, Peng; Feng, Yuelin; et al. (Frontiers in Earth Science, 2022)
Multi-stage hydrocarbon generation and accumulation are very common in petroliferous basins. Also, determination of hydrocarbon accumulation stages and each related diagenetic feature is important for understanding the distribution of current oil and gas resources in one individual basin. However, in the case of conventional sandstone reservoirs, few studies have focused on these resulting reservoir features (e.g., physical property and wettability) that are caused by the first accumulation of hydrocarbons and their geological implications. In this study, taking the reservoir from the Eocene Dongying Depression as an example, we investigated the features of the early hydrocarbon accumulation and its effects on the late accumulation, by analyzing the early accumulation-related paragenesis, fluid inclusions, clay minerals content, reservoir physical property, and wettability in sandstones. Our results show that the early stage accumulation of the overpressured hydrocarbon fluid could support and offset some loads of overburden, weaken the normal compaction, and preserve some original pores. Also, the early hydrocarbon accumulation resulted in an alternated, diagenetic fluid environment from the initial acidic to subsequent alkalic conditions, with the overall dissolution intensity stronger than the cementation, and formed a large number of secondary pores. As a result, the early accumulation was beneficial to reservoir space development and provided more space for the late hydrocarbons. In addition, the early hydrocarbon accumulation could cause the alteration of rock wettability and gradually formed a lipophilic migration pathway from the source rock to the reservoir. Also, the late stage of hydrocarbons would preferentially choose this dominant pathway for their migration (i.e., inheritance of migration pathway).